Analysis of caffeine as a treatment for attention deficit disorder with hyperactivity: a literature review (Research, Society and Development, 2022)
Introduction: Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder that affects children, adults and the elderly worldwide, with multifactorial origins. Currently, therapy is performed with drugs derived from amphetamines, however, other substances have received attention, such as caffeine, which has pharmacological action through antagonism of adenosine receptors, being a possible treatment for ADHD. Objective: To analyze the possible effects of caffeine as a possible therapeutic option in ADHD. Methodology: This is a literature review focusing on the analysis of the effects of caffeine as a possible treatment for ADHD. Using descriptors like "caffeine"; "ADHD"; "therapeutics"; “methylphenidate” and “attention hyperactivity disorder” in the Scientific Electronic Library of Medicine (SCIELO), National Library of Medicine (PubMed MEDLINE) and Virtual Health Library (BVS) databases. Results and Discussion: Caffeine, when administered together with amphetamines, tended to be potentiated by caffeine due to cross-sensitization. In rodents, they showed significant results in alertness. In humans, positive results have also been demonstrated by facilitating the release of neurotransmitters responsible for controlling motor functions and well-being. Conclusion: Although there are benefits of caffeine in the treatment of the disorder, however, caffeine had certain adverse effects, in addition to the fact that there are not many current studies in humans. For this, further studies in humans are needed to prove its efficacy and safety in ADHD, contributing to the therapeutic evolution of this disorder.